Quantum dot-based lens material and preparation method and application thereof
By using quantum dot precursors in the LED backlight module to microwave polymerize with acrylic compounds and initiators, a polymer-covered quantum dots is formed, and combined with quantum dot stabilizers, the problems of quantum dot dispersion and stability are solved, and the problem of quantum dot dispersion and stability is achieved. Efficient luminous efficiency and stability, suitable for LED backlight modules.
Patent Information
- Application Number
- CN202411488643.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-24
- Publication Date
- 2024-12-31
- Estimated Expiration
- 2044-10-24
AI Technical Summary
The dispersion and stability of quantum dots in LED backlight modules limit their application.
Using a lens material based on quantum dots, the quantum dot precursor is microwave polymerized with acrylic compounds and initiators to form a polymer-covered quantum dot, and combined with a quantum dot stabilizer, the stability and luminous efficiency of the quantum dot are improved.
Improve the stability and luminous efficiency of quantum dot lens materials, the photoluminescence quantum yield is greater than 60%, the brightness attenuation is less than 15%, and the light transmittance is still greater than 90%, which solves the application of quantum dots in LED backlight modules. Dispersion and stability issues.
Smart Images

Figure BDA0005099380100000081 
Figure BDA0005099380100000091
Abstract
Description
Technical Field
[0001] The present invention relates to the field of quantum dot materials, and in particular to a quantum dot-based lens material and a preparation method and application thereof. Background Art
[0002] Quantum dots (QD) are a new type of luminescent material with the advantages of narrow luminescence spectrum, wide excitation spectrum, high quantum yield and solution preparation. The light-emitting diode (LED) device made of them can achieve narrow emission half-wave peaks (<20nm) in the red, blue and green bands through the color conversion process, and the color gamut range exceeds 120% NTSC.
[0003] According to the different positions of quantum dots in the backlight structure, quantum dot backlight technology is mainly divided into three types: the first is to replace the phosphor material with quantum dots and directly package it together with the LED chip; the second is to sandwich the quantum dots between two layers of water-proof and oxygen-proof films to form a "sandwich" quantum dot film, and attach it directly above the light guide plate; the third is to encapsulate the quantum dots in a special glass tube in a water-proof and oxygen-proof environment and install it at the incident point of the backlight LED. All three technologies have their own advantages and disadvantages.
[0004] However, in the prior art, the dispersion and stability of quantum dots are the main problems that limit their application in LED backlight modules. Summary of the invention
[0005] In order to solve the above problems, the first aspect of the present invention provides a quantum dot-based lens material, and the preparation raw materials include: a quantum dot precursor, an acrylic compound, an initiator, and a quantum dot stabilizer.
[0006] The raw materials for preparing the quantum dot precursor include: a cadmium source solution, a sulfur source solution, an oxysilane substance, and a sulfonate substance.
[0007] The cadmium source is selected from at least one of cadmium oxide, cadmium nitrate and cadmium chloride; the sulfur source is selected from at least one of sulfur powder, sodium sulfide, cysteine and thioacetamide.
[0008] The cadmium source or sulfur source in the raw material for preparing the quantum dot precursor can be replaced by, but not limited to, phosphides (such as boron phosphide, aluminum phosphide, copper phosphide, gallium phosphide, indium phosphide), nitrides (such as aluminum nitride, gallium nitride, indium nitride, silicon nitride, germanium nitride), sulfides (such as cadmium sulfide, mercury sulfide, beryllium sulfide, magnesium sulfide, germanium sulfide, tin sulfide, lead sulfide, zinc sulfide), selenides (such as lead selenide, cadmium selenide, mercury selenide, beryllium selenide, magnesium selenide, germanium selenide, tin selenide, zinc selenide), tellurides (such as lead telluride, cadmium telluride, germanium telluride, mercury telluride, beryllium telluride, tin telluride, zinc telluride), halides (copper bromide, copper iodide), metal oxides (such as aluminum oxide, lead oxide, zinc oxide), and other raw materials for preparing other quantum dots.
[0009] The oxysilane substance is selected from at least one of propyltrimethoxysilane, butyltrimethoxysilane, 3-acryloxypropyltriethoxysilane, and N,N-diethyl-3-aminopropylmethyldimethoxysilane.
[0010] The sulfonate substance is selected from at least one of 1,4-dioctadecyl sodium sulfosuccinate, sodium dodecylbenzene sulfonate, sodium 4-tetradecylbenzene sulfonate and sodium 2-(trimethylsilyl)ethane sulfonate.
[0011] The initiator is selected from persulfates, azo compounds or peroxides.
[0012] The quantum dot stabilizer is selected from at least one of n-hexane, dimethyl sulfoxide, oleic acid, oleylamine, chloroform, and isobornyl acrylate.
[0013] The method for preparing the quantum dot-based lens material comprises the following steps:
[0014] S1. Add water to the quantum dot precursor and wet grind to obtain a mixture, wherein the weight ratio of the quantum dot precursor to water is 1-5%;
[0015] S2, mixing the mixture with an acrylic compound, and stirring at 500-1000 r / min to form an emulsion;
[0016] S3, adding an initiator into the emulsion to carry out microwave polymerization;
[0017] S4. After the polymerization is completed, the product is filtered, dried, and a quantum dot stabilizer is added to obtain a quantum dot-based lens material.
[0018] In step S1, the preparation method of the quantum dot precursor is: mixing the cadmium source solution and the sulfur source solution, ultrasonicating for 10-30 minutes, and then adding oxysilane substances and sulfonate substances, wherein the total concentration of the added oxysilane substances and sulfonate substances is 0.5-2g / L.
[0019] Preferably, in step S1, the preparation method of the quantum dot precursor is: 100 mL of cadmium source solution and 100 mL of sulfur source solution are mixed and ultrasonicated for 10-30 minutes, and then 3-acryloxypropyl triethoxysilane, sodium 4-(2-methylprop-2-enyloxy)benzenesulfonate and sodium dodecylbenzenesulfonate are added. Wherein: the total concentration of the added 3-acryloxypropyl triethoxysilane, sodium 4-(2-methylprop-2-enyloxy)benzenesulfonate and sodium dodecylbenzenesulfonate is 1g / L, and the weight ratio of 3-acryloxypropyl triethoxysilane, sodium 4-(2-methylprop-2-enyloxy)benzenesulfonate and sodium dodecylbenzenesulfonate solution is 1:1:2.
[0020] The cadmium source solution is an ethanol solution of cadmium chloride and / or cadmium nitrate, with a concentration of 1 g / mL; the sulfur source solution is an aqueous solution of cysteine.
[0021] In step S2, the acrylic compound includes methyl methacrylate and tert-butyl methacrylate; wherein the weight ratio of the mixture to the acrylic compound is 5:1, and the weight ratio of methyl methacrylate to tert-butyl methacrylate is 1:1.
[0022] In step S3, the initiator is selected from persulfate, azo compound or peroxide, such as potassium persulfate, sodium bisulfate, sodium azide, oxybenzoyl, azobisisobutyronitrile, dimethyl azobisisobutyrate, etc. The weight of the initiator accounts for 1-8‰ of the weight of the acrylic compound.
[0023] The microwave power is 100-480W, and the time is 1-20min.
[0024] The present application combines microwave technology with dimethyl azobisisobutyrate initiator to enable methyl methacrylate, tert-butyl methacrylate, etc. to polymerize faster, thus accelerating the reaction speed. At the same time, the prepared quantum dots are well coated in the polymer, thus improving the stability of the quantum dots.
[0025] Beneficial effects: The preparation method of the present application is simple and low-cost. Through the interaction of 3-acryloxypropyl triethoxysilane, sodium 4-(2-methylprop-2-enyloxy) benzene sulfonate, sodium dodecylbenzene sulfonate and cadmium source and sulfur source, 3-acryloxypropyl triethoxysilane, sodium 4-(2-methylprop-2-enyloxy) benzene sulfonate and acrylic compounds are polymerized to prepare a polymer-coated quantum dot lens material. The polymer coating can well isolate oxygen and moisture, avoid quantum dot fluorescence quenching and inactivation, and improve the stability of the quantum dot lens material. And the luminous efficiency is high, the photoluminescence quantum yield (PLQY) is greater than 60%, the brightness decay is less than 15% after photothermal aging, and the transmittance is still greater than 90%. DETAILED DESCRIPTION
[0026] The present invention is specifically described below by way of examples.
[0027] If not stated otherwise, all starting materials used were commercially available.
[0028] Example
[0029] Example 1
[0030] The method for preparing a lens material based on quantum dots comprises the following steps:
[0031] S1. Adding water to the quantum dot precursor and mixing and wet grinding to obtain a mixture, wherein the weight ratio of the quantum dot precursor to water is 3%;
[0032] S2, mixing the mixture with an acrylic compound, and stirring at 800 r / min to form an emulsion;
[0033] S3, adding an initiator into the emulsion to carry out microwave polymerization;
[0034] S4. After the polymerization is completed, the product is filtered, dried, and a quantum dot stabilizer is added to obtain a quantum dot-based lens material.
[0035] In step S1, the preparation method of the quantum dot precursor is: 100 mL of cadmium source solution and 100 mL of sulfur source solution are mixed and ultrasonicated for 20 minutes, and then 3-acryloxypropyl triethoxysilane, sodium 4-(2-methylprop-2-enyloxy)benzenesulfonate and sodium dodecylbenzenesulfonate are added. Wherein: the total concentration of the added 3-acryloxypropyl triethoxysilane, sodium 4-(2-methylprop-2-enyloxy)benzenesulfonate and sodium dodecylbenzenesulfonate is 1g / L, and the weight ratio of 3-acryloxypropyl triethoxysilane, sodium 4-(2-methylprop-2-enyloxy)benzenesulfonate and sodium dodecylbenzenesulfonate solution is 1:1:2.
[0036] The cadmium source solution is an ethanol solution of cadmium chloride with a concentration of 1 g / mL; the sulfur source solution is an aqueous solution of cysteine with a molar ratio of cadmium chloride to cysteine of 0.5:1.
[0037] In step S2, the acrylic compound includes methyl methacrylate and tert-butyl methacrylate; wherein the weight ratio of the mixture to the acrylic compound is 5:1, and the weight ratio of methyl methacrylate to tert-butyl methacrylate is 1:1.
[0038] In step S3, the initiator is dimethyl azobisisobutyrate, and the weight of the initiator accounts for 5‰ of the weight of the acrylic compound.
[0039] The microwave power is 240 W, and the time is 10 min.
[0040] Example 2
[0041] The method for preparing a lens material based on quantum dots comprises the following steps:
[0042] S1. Adding water to the quantum dot precursor and mixing and wet grinding to obtain a mixture, wherein the weight ratio of the quantum dot precursor to water is 1%;
[0043] S2, mixing the mixture with an acrylic compound, and stirring at 500 r / min to form an emulsion;
[0044] S3, adding an initiator into the emulsion to carry out microwave polymerization;
[0045] S4. After the polymerization is completed, the product is filtered, dried, and a quantum dot stabilizer is added to obtain a quantum dot-based lens material.
[0046] In step S1, the preparation method of the quantum dot precursor is: 100 mL of cadmium source solution and 100 mL of sulfur source solution are mixed and ultrasonicated for 10 minutes, and then 3-acryloxypropyl triethoxysilane, sodium 4-(2-methylprop-2-enyloxy)benzenesulfonate and sodium dodecylbenzenesulfonate are added. Wherein: the total concentration of the added 3-acryloxypropyl triethoxysilane, sodium 4-(2-methylprop-2-enyloxy)benzenesulfonate and sodium dodecylbenzenesulfonate is 1g / L, and the weight ratio of 3-acryloxypropyl triethoxysilane, sodium 4-(2-methylprop-2-enyloxy)benzenesulfonate and sodium dodecylbenzenesulfonate solution is 1:1:2.
[0047] The cadmium source solution is an ethanol solution of cadmium chloride and / or cadmium nitrate, with a concentration of 1 g / mL; the sulfur source solution is an aqueous solution of cysteine, with a molar ratio of cadmium chloride to cysteine of 0.5:1.
[0048] In step S2, the acrylic compound includes methyl methacrylate and tert-butyl methacrylate; wherein the weight ratio of the mixture to the acrylic compound is 5:1, and the weight ratio of methyl methacrylate to tert-butyl methacrylate is 1:1.
[0049] In step S3, the initiator is dimethyl azobisisobutyrate, etc. The weight of the initiator accounts for 5‰ of the weight of the acrylic compound.
[0050] The microwave power is 100 W, and the time is 20 min.
[0051] Example 3
[0052] The method for preparing a lens material based on quantum dots comprises the following steps:
[0053] S1. Adding water to the quantum dot precursor and mixing and wet grinding to obtain a mixture, wherein the weight ratio of the quantum dot precursor to water is 5%;
[0054] S2, mixing the mixture with an acrylic compound, and stirring at 1000 r / min to form an emulsion;
[0055] S3, adding an initiator into the emulsion to carry out microwave polymerization;
[0056] S4. After the polymerization is completed, the product is filtered, dried, and a quantum dot stabilizer is added to obtain a quantum dot-based lens material.
[0057] In step S1, the preparation method of the quantum dot precursor is: 100 mL of cadmium source solution and 100 mL of sulfur source solution are mixed and ultrasonicated for 30 minutes, and then 3-acryloxypropyl triethoxysilane, sodium 4-(2-methylprop-2-enyloxy)benzenesulfonate and sodium dodecylbenzenesulfonate are added. Wherein: the total concentration of the added 3-acryloxypropyl triethoxysilane, sodium 4-(2-methylprop-2-enyloxy)benzenesulfonate and sodium dodecylbenzenesulfonate is 1g / L, and the weight ratio of 3-acryloxypropyl triethoxysilane, sodium 4-(2-methylprop-2-enyloxy)benzenesulfonate and sodium dodecylbenzenesulfonate solution is 1:1:2.
[0058] The cadmium source solution is an ethanol solution of cadmium chloride and / or cadmium nitrate, with a concentration of 1 g / mL; the sulfur source solution is an aqueous solution of cysteine, with a molar ratio of cadmium chloride to cysteine of 0.5:1.
[0059] In step S2, the acrylic compound includes methyl methacrylate and tert-butyl methacrylate; wherein the weight ratio of the mixture to the acrylic compound is 5:1, and the weight ratio of methyl methacrylate to tert-butyl methacrylate is 1:1.
[0060] In step S3, the initiator is selected from persulfate, azo compound or peroxide, such as potassium persulfate, sodium bisulfate, sodium azide, oxybenzoyl, azobisisobutyronitrile, dimethyl azobisisobutyrate, etc. The weight of the initiator accounts for 8‰ of the weight of the acrylic compound.
[0061] The microwave power is 480 W, and the time is 5 min.
[0062] Comparative Example 1
[0063] The method for preparing a lens material based on quantum dots comprises the following steps:
[0064] S1. Adding water to the quantum dot precursor and mixing and wet grinding to obtain a mixture, wherein the weight ratio of the quantum dot precursor to water is 3%;
[0065] S2, mixing the mixture with an acrylic compound, and stirring at 800 r / min to form an emulsion;
[0066] S3, adding an initiator into the emulsion to carry out microwave polymerization;
[0067] S4. After the polymerization is completed, the product is filtered, dried, and a quantum dot stabilizer is added to obtain a quantum dot-based lens material.
[0068] In step S1, the preparation method of the quantum dot precursor is: 100 mL of cadmium source solution and 100 mL of sulfur source solution are mixed, ultrasonicated for 20 minutes, and then sodium dodecylbenzene sulfonate is added, wherein: the total concentration of sodium dodecylbenzene sulfonate after addition is 1 g / L.
[0069] The cadmium source solution is an ethanol solution of cadmium chloride with a concentration of 1 g / mL; the sulfur source solution is an aqueous solution of cysteine with a molar ratio of cadmium chloride to cysteine of 0.5:1.
[0070] In step S2, the acrylic compound includes methyl methacrylate and tert-butyl methacrylate; wherein the weight ratio of the mixture to the acrylic compound is 5:1, and the weight ratio of methyl methacrylate to tert-butyl methacrylate is 1:1.
[0071] In step S3, the initiator is dimethyl azobisisobutyrate, and the weight of the initiator accounts for 5‰ of the weight of the acrylic compound.
[0072] The microwave power is 240 W, and the time is 10 min.
[0073] Comparative Example 2
[0074] The method for preparing a lens material based on quantum dots comprises the following steps:
[0075] S1. Adding water to the quantum dot precursor and mixing and wet grinding to obtain a mixture, wherein the weight ratio of the quantum dot precursor to water is 3%;
[0076] S2, mixing the mixture with an acrylic compound, and stirring at 800 r / min to form an emulsion;
[0077] S3, adding an initiator into the emulsion to carry out microwave polymerization;
[0078] S4. After the polymerization is completed, the product is filtered, dried, and a quantum dot stabilizer is added to obtain a quantum dot-based lens material.
[0079] In step S1, the preparation method of the quantum dot precursor is: 100 mL of cadmium source solution and 100 mL of sulfur source solution are mixed and ultrasonicated for 20 minutes, and then 3-acryloxypropyl triethoxysilane and sodium dodecylbenzene sulfonate are added. Wherein: after the addition, the overall concentration of 3-acryloxypropyl triethoxysilane and sodium dodecylbenzene sulfonate is 1 g / L, and the weight ratio of 3-acryloxypropyl triethoxysilane to sodium dodecylbenzene sulfonate solution is 1:2.
[0080] The cadmium source solution is an ethanol solution of cadmium chloride with a concentration of 1 g / mL; the sulfur source solution is an aqueous solution of cysteine with a molar ratio of cadmium chloride to cysteine of 0.5:1.
[0081] In step S2, the acrylic compound includes methyl methacrylate and tert-butyl methacrylate; wherein the weight ratio of the mixture to the acrylic compound is 5:1, and the weight ratio of methyl methacrylate to tert-butyl methacrylate is 1:1.
[0082] In step S3, the initiator is dimethyl azobisisobutyrate, and the weight of the initiator accounts for 5‰ of the weight of the acrylic compound.
[0083] The microwave power is 240 W, and the time is 10 min.
[0084] Comparative Example 3
[0085] The method for preparing a lens material based on quantum dots comprises the following steps:
[0086] S1. Adding water to the quantum dot precursor and mixing and wet grinding to obtain a mixture, wherein the weight ratio of the quantum dot precursor to water is 3%;
[0087] S2, mixing the mixture with an acrylic compound, and stirring at 800 r / min to form an emulsion;
[0088] S3, adding an initiator into the emulsion to carry out microwave polymerization;
[0089] S4. After the polymerization is completed, the product is filtered, dried, and a quantum dot stabilizer is added to obtain a quantum dot-based lens material.
[0090] In step S1, the preparation method of the quantum dot precursor is: 100 mL of cadmium source solution and 100 mL of sulfur source solution are mixed and ultrasonicated for 20 minutes, and then 3-acryloxypropyl triethoxysilane, sodium 4-(2-methylprop-2-enyloxy)benzenesulfonate and sodium dodecylbenzenesulfonate are added. Wherein: the overall concentration of 3-acryloxypropyl triethoxysilane, sodium 4-(2-methylprop-2-enyloxy)benzenesulfonate and sodium dodecylbenzenesulfonate after addition is 1g / L, and the weight ratio of 3-acryloxypropyl triethoxysilane, sodium 4-(2-methylprop-2-enyloxy)benzenesulfonate and sodium dodecylbenzenesulfonate solution is 1:1:2.
[0091] The cadmium source solution is an ethanol solution of cadmium chloride with a concentration of 1 g / mL; the sulfur source solution is an aqueous solution of cysteine with a molar ratio of cadmium chloride to cysteine of 0.5:1.
[0092] In step S2, the acrylic compound is methyl methacrylate, tert-butyl methacrylate, and 2-butyloctyl methacrylate; wherein the weight ratio of the mixture to the acrylic compound is 5:1, and the weight ratio of methyl methacrylate, tert-butyl methacrylate, and 2-butyloctyl methacrylate is 1:1:1.
[0093] In step S3, the initiator is dimethyl azobisisobutyrate, and the weight of the initiator accounts for 5‰ of the weight of the acrylic compound.
[0094] The microwave power is 240 W, and the time is 10 min.
[0095] Performance Testing
[0096] The lens material prepared in Example 1-3 or Comparative Example 1-3 is added to toluene, and then the PMMA solution is added, and the mixture is heated and stirred evenly to obtain a quantum dot colloidal material, wherein the mass fraction of the material prepared in Example 1-3 or Comparative Example 1-3 is 5%, the mass fraction of the resin material is 85%, and the mass fraction of the solvent is 10%; the quantum dot colloidal material is then injected into a lens mold and cured to obtain a QD lens. The QD lens is placed between a common expansion board and an LED lamp bead, and the performance is tested after being fixed.
[0097] The photoluminescence quantum yield (PLQY) of Examples 1-3 was tested to be greater than 60%. The photoluminescence quantum yield (PLQY) refers to the ratio of the number of emitted photons to the number of absorbed photons.
[0098] After the prepared OD lens was placed at 60°C and 90% RH for 1000 hours, its brightness attenuation was tested. The specific test results are shown in the table below. It can be seen that the brightness attenuation of the QD lens is small after aging. Moreover, after aging treatment, the transmittance of the QD lens is still greater than 90%.
[0099]
[0100]
[0101] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A quantum dot-based lens material, characterized in that: The preparation raw materials include: quantum dot precursor, acrylic compound, initiator, quantum dot stabilizer; The raw materials for preparing the quantum dot precursor include: a cadmium source solution, a sulfur source solution, an oxysilane substance, and a sulfonate substance; The cadmium source is selected from at least one of cadmium oxide, cadmium nitrate and cadmium chloride; the sulfur source is selected from at least one of sulfur powder, sodium sulfide, cysteine and thioacetamide.
2. The quantum dot-based lens material according to claim 1, characterized in that: The oxysilane substance is selected from at least one of propyltrimethoxysilane, butyltrimethoxysilane, 3-acryloxypropyltriethoxysilane, and N,N-diethyl-3-aminopropylmethyldimethoxysilane.
3. The quantum dot-based lens material according to claim 1, characterized in that: The sulfonate substance is selected from at least one of 1,4-dioctadecyl sodium sulfosuccinate, sodium dodecylbenzene sulfonate, sodium 4-tetradecylbenzene sulfonate and sodium 2-(trimethylsilyl)ethane sulfonate.
4. The quantum dot-based lens material according to claim 1, characterized in that: The quantum dot stabilizer is selected from at least one of n-hexane, dimethyl sulfoxide, oleic acid, oleylamine, chloroform, and isobornyl acrylate.
5. A method for preparing a quantum dot-based lens material according to any one of claims 1 to 4, characterized in that: The following steps are involved: S1. Add water to the quantum dot precursor and wet grind to obtain a mixture, wherein the weight ratio of the quantum dot precursor to water is 1-5%; S2, mixing the mixture with an acrylic compound, and stirring at 500-1000 r / min to form an emulsion; S3, adding an initiator into the emulsion to carry out microwave polymerization; S4. After the polymerization is completed, the product is filtered, dried, and a quantum dot stabilizer is added to obtain a quantum dot-based lens material.
6. The method for preparing a quantum dot-based lens material according to claim 5, characterized in that: In step S1, the preparation method of the quantum dot precursor is: mixing the cadmium source solution and the sulfur source solution, ultrasonicating for 10-30 minutes, and then adding oxysilane substances and sulfonate substances, wherein the total concentration of the added oxysilane substances and sulfonate substances is 0.5-2g / L.
7. The method for preparing a quantum dot-based lens material according to claim 6, characterized in that: The cadmium source solution is an ethanol solution of cadmium chloride and / or cadmium nitrate; and the sulfur source solution is an aqueous solution of cysteine.
8. The method for preparing a quantum dot-based lens material according to claim 6, wherein: The acrylic compound includes methyl methacrylate and tert-butyl methacrylate; wherein the weight ratio of the mixture to the acrylic compound is 5:
1.
9. The method for preparing a quantum dot-based lens material according to claim 8, characterized in that: The weight ratio of methyl methacrylate to tert-butyl methacrylate is 1:
1.
10. Use of the quantum dot-based lens material according to any one of claims 1 to 4 in an LED backlight module.
Citation Information
Patent Citations
Quantum dot / polymer composite nitric oxide fluorescent probe and preparation method thereof
CN102585417A
AgInS2 quantum dot / PMMA (Polymethyl Methacrylate) composite luminescent material and application thereof
CN104263361A
Preparation method of water soluble cadmium sulfide quantum dots
CN104876257A
Method for preparing graphene-quantum dot composite material
CN105399080A
Optimized processing method for fluorescent quantum dots
CN109609114A
